2021
DOI: 10.3390/w13060756
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Flood Damage in Urban Areas Using RCP 8.5 Climate Change Scenarios and Building Inventory

Abstract: Korea has frequent flood damage due to localized torrential rain and typhoons as a result of climate change, which causes many casualties and property damage. In particular, much damage occurs due to urban inundation caused by stream flooding as a result of climate change. Thus, this study aims to analyze the effect of climate change on flood damage targeting the Wonjucheon basin, which is an urban stream flowing the city. For future rainfall data, RCP (Representative Concentration Pathways) 8.5 climate change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The similar explanation can also be understood in the decrease of students' curiosity attitudes (RG = -0.26), that the habit of students who constantly experience tidal floods affects their behaviour and attitudes towards environmental issues. This is in line with research conducted by Kang et al (2021) which shows that people living in flood-prone areas tend to experience higher psychological fatigue, which can ultimately reduce their interest in environmental issues.…”
Section: Categorysupporting
confidence: 90%
“…The similar explanation can also be understood in the decrease of students' curiosity attitudes (RG = -0.26), that the habit of students who constantly experience tidal floods affects their behaviour and attitudes towards environmental issues. This is in line with research conducted by Kang et al (2021) which shows that people living in flood-prone areas tend to experience higher psychological fatigue, which can ultimately reduce their interest in environmental issues.…”
Section: Categorysupporting
confidence: 90%
“…The statistical downscaling method has been applied to macro cases by Fiseha et al [28] to analyze the impact of climate change on the basin of the Tiber River. Kang et al [29] did the same thing in 2021 to look at projected possible flooding in South Korean urban areas.…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies on flood inundation include the inundation of inland cities caused by rainstorm, and the possible inundation area could be calculated by rainfall to calculate the possible property loss [28]. In addition, the previous study also suggested that the inundation range of flood may increase by about 30% due to the increase of river flood [29].…”
Section: Introductionmentioning
confidence: 99%